2013
DOI: 10.1002/cbic.201300427
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Oxidative Routes towards the Maturation of Nosiheptide

Abstract: Three oxidative routes: Two cytochrome P450‐like mono‐oxygenases cooperate in the biosynthesis of nosiheptide (Nos): NosB catalyzes hydroxylation of the Glu6 γ‐position, whereas NosC hydroxylates the Pyr3 position, thus enabling cleavage of the bis‐Dha tail by NosA. Combining the polysubstrate specificity of NosB and NosC and the function of NosA generates three oxidative routes in nosiheptide maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…Currently, these include thiocillin, 52, 54, 249, 250 thiostrepton, 54, 56, 251 siomycin, 54 nosiheptide, 53, 252, 253 GE2270, 55, 254, 255 thiomuracin, 45, 55 nocathiacin, 256, 257 cyclothiazomycin, 258, 259 TP-1161, 260 GE37468, 261 berninamycin, 262 lactocillin, 263 nocardithiocin, 264 and lactazole. 265 Many natural congeners of these compounds are known to be produced by the same BGC.…”
Section: Thiopeptidesmentioning
confidence: 99%
“…Currently, these include thiocillin, 52, 54, 249, 250 thiostrepton, 54, 56, 251 siomycin, 54 nosiheptide, 53, 252, 253 GE2270, 55, 254, 255 thiomuracin, 45, 55 nocathiacin, 256, 257 cyclothiazomycin, 258, 259 TP-1161, 260 GE37468, 261 berninamycin, 262 lactocillin, 263 nocardithiocin, 264 and lactazole. 265 Many natural congeners of these compounds are known to be produced by the same BGC.…”
Section: Thiopeptidesmentioning
confidence: 99%
“…5E ). These observations are supported by the fact that the catalytic power of NosA was completely abolished after removing these two hydroxyl groups in the substrate 17 . Moreover, the –OH group in pyridine ring is obviously more acidic than –OH group next to the carbonyl group in the substrate, which could interpret why the side-chain of residue K49 of NosA easily interacts with the –OH group in pyridine ring.…”
Section: Resultsmentioning
confidence: 65%
“…It was reported that the removal of two –OH groups on the substrate (highlighted in red and in blue in Fig. 1 , respectively) (by knockouting the genes nosC and nosB in nosiheptide biosynthesis responsible for these –OH groups formation, respectively) made NosA completely lose the catalytic activities 17 , suggesting that these two –OH groups in the substrate are important for the catalytic reaction. Interestingly, as shown in supporting information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biosynthetic gene cluster of nosiheptide was elucidated in 2009 (21). Several groups have focused on the biosynthesis of nosiheptide, and progress has subsequently been made (26)(27)(28)(29)(30)(31)(32)(33). However, these studies have been limited to only the late modification stage without the involvement of the leader peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the functions or roles of the leader peptide could certainly provide an insightful basis to reveal all of the biosynthetic steps in nosiheptide biosynthesis. In addition, based on the feasibility of genetic manipulation in S. actuosus ATCC 25421, exploration of the roles of the leader peptide in the biosynthetic gene cluster of nosiheptide has become approachable (21,27,28).…”
Section: Discussionmentioning
confidence: 99%